Association between socioeconomic factors and cancer risk: a population cohort study in Scotland (1991-2006). - Katharine H Sharpe; Alex D McMahon; Gillian M Raab; David H Brewster; David I Conway (PLoS ONE)
Background Lung and upper aero-digestive tract (UADT) cancer risk are associated with low socioeconomic circumstances and routinely measured using area socioeconomic indices. We investigated effect of country of birth, marital status, one area deprivation measure and individual socioeconomic variables (economic activity, education, occupational social class, car ownership, household tenure) on risk associated with lung, UADT and all cancer combined (excluding non melanoma skin cancer). Methods We linked Scottish Longitudinal Study and Scottish Cancer Registry to follow 203,658 cohort members aged 15+ years from 1991-2006. Relative risks (RR) were calculated using Poisson regression models by sex offset for person-years of follow-up. Results 21,832 first primary tumours (including 3,505 lung, 1,206 UADT) were diagnosed. Regardless of cancer, economically inactivity (versus activity) was associated with increased risk (male: RR 1.14, 95% CI 1.10-1.18; female: RR 1.06, 95% CI 1.02-1.11). For lung cancer, area deprivation remained significant after full adjustment suggesting the area deprivation cannot be fully explained by individual variables. No or non degree qualification (versus degree) was associated with increased lung risk; likewise for UADT risk (females only). Occupational social class associations were most pronounced and elevated for UADT risk. No car access (versus ownership) was associated with increased risk (excluding all cancer risk, males). Renting (versus home ownership) was associated with increased lung cancer risk, UADT cancer risk (males only) and all cancer risk (females only). Regardless of cancer group, elevated risk was associated with no education and living in deprived areas. Conclusions Different and independent socioeconomic variables are inversely associated with different cancer risks in both sexes; no one socioeconomic variable captures all aspects of socioeconomic circumstances or life course. Association of multiple socioeconomic variables is likely to reflect the complexity and multifaceted nature of deprivation as well as the various roles of these dimensions over the life course.